IMPLEMENTASI PERATURAN WALIKOTA NOMOR 31 TAHUN 2006 TENTANG PEMBEBASAN BIAYA ATAS PEMBUATAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SAMARINDA - Fahmy Fakhrozy (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The result shows that implementation of birth certificate service at Disdukcapil Samarinda has a clear procedure, a secure process, a timeliness conducted by capable employees and supported by good infrastructure which goes with the people expectation. Meanwhile at the same time Disdukcapil Samarinda also supported by the strong policy in managing citizenship administration services, good coordination between the employees and a condusive work environment.